Quality management system for laser equipment: The experience of USL Umbria 2. (September 2016) - Paolucci, M.; Di Lorenzo, R.; Didona, A.; Lotti, E.
Abstract : Introduction: The development process of USL Umbria 2 Quality Management System (QMS) led, from 2008, to ISO9001:2008 Certification of the Medical Physics Department (MPD) activities. Purpose: In this framework, in addition to the application of its own QMS, the MPD works in partnerships with all departments and structures which use ionizing and non-ionizing radiation facilities included medical LASER equipment. Materials and methods: QMS for LASER equipment consists of: Design of work processes, with realization of the related forms and safety signs. Recognition of laser equipment and environmental and individual protection devices within our medical institution. Realization of a dedicated Quality Assurance program, with the implementation of a technical protocol, planning and execution of quality and functional tests using calibrated measuring devices, recording and storage system of Quality Controls performed. Design and realization of Laser Safety Management System with draft of Safety Guidance and training course program for hospital staff exposed to LASER risks. Results: Our project has been performed over a period of about six years, its application led to an optimization of the distribution of the LASER equipment in all the USL Umbria 2 health facilities (17 structures, including hospitals and health districts), where classes 3B and 4 LASER equipment are installed and used for various applications. Conclusions: The quality and functional checks, included staff training, have highlighted the need to continuous verification in order to provide the proper protection to patients and operators during clinical activities.